Developing a mathematical modeling method for determining the potential rates of microbial ammonia oxidation and nitrite oxidation in environmental samples. (September 2018) - Hong, Yiguo; Wang, Yan; Wu, Jiapeng; Jiao, Lijing; He, Xiang; Wen, Xiaomei; Zhang, Hongguo; Chang, Xiangyang
Abstract: This study report a new method for simultaneously determining microbial ammonia oxidation rate (Va ) and nitrite oxidation rate (Vn ) in water and sediment. This method is based on mathematical modeling analysis for the time series variation of DIN (nitrite, nitrate, and ammonium) in an incubation system without an inhibitor. Compared to the traditional methods with specific inhibitors, this method is not affected by inhibitors and can determine both instantaneous and average Va and Vn accurately and simultaneously. Practical application indicated that this method can well determine the dynamic variations in Va and Vn in both water and sediment samples. Highlights: Developed a new method for determining microbial nitrification rate. This method can determine both instantaneous and average rates accurately. This method is based on mathematical modeling analysis.